PENGABDIAN MASYARAKAT DALAM PENGUATAN PENDIDIKAN KEAGAMAAN DAN SOSIAL - Fitriani, Fitriani; Rahmatiah, Rahmatiah; Hardianti Ilyas, Diyan; Syamsinar, Syamsinar; Nurhimaya, Nurhimaya; Rahmawati Tamrin, ST.; Sukmawati Atjo, Andi (Universitas Muhammadiyah Tapanuli Selatan, 2025)
Kegiatan pengabdian masyarakat bertajuk